IDENTIFICATION OF MEDICINE PLANTS IN THE SRIWIJAYA BOTANICAL GARDEN, BAKUNG VILLAGE, INDRALAYA UTARA DISTRICT, OGAN ILIR REGENCY, SOUTH SUMATRA PROVINCE - Syahroni, Sasua Hustati; Helida, Asvic; Jaya, Amer (Sylva : Jurnal Penelitian Ilmu-Ilmu Kehutanan, 2021)
This study aims to determine and identify the composition and type of structure medicinal plants in the Sriwijaya botanical garden through analysis of medicinal plant vegetation by using a species diversity index. The research method used was a survey with a sampling technique used was a sampling method or intentionally from the area of the Sriwijaya Botanical Garden conservation area. Using the formula for sampling intensity [IS] of 2% and a total area of 100 Ha, the number of sample plots obtained is 50. This study identified 43 families and 76 species of medicinal plants. The highest importance index (INP) of the lower plants in the lower plantswas Senduduk (Melastoma malabathricum) a value 29,797%, while the lowest INP is Cataract (Laurentia longifora), Curry Leaf (Murraya koenigii), Kumis Kucing (Orthosiphon aristatus) a 0,724%. While in INP, the highest mastery of medicinal plants at sapling level is Jelutung (Dyera costulata) a value 40.741%, while the lowest INP a butterfly (Bauhinia porpurea) with 4.204%. The diversity indexes of medicinal plants at the understorey and sapling levels were found to be 2.00 and 1.03, in both, indicating that understorey and sapling diversity was moderate and the community state was very stable. While the diversity index of medicinal plants at the seedling level was 0.94, indicating that medicinal plant diversity at the seedling stage is poor and the community state is quite poor.